Estimating Methane Emission from Floating Net Cage Fish Farming in Sutami Reservoir, Indonesia - Syadzadhiya Qothrunada Zakiyayasin Nisa; Praditya Sigit Ardisty Sitogasa; Mohamad Mirwan (Future Science)
Reservoirs are commonly used for aquaculture with floating net cage systems. The fish feed is not all eaten by the fish, so it is wasted to the bottom of the reservoir as uneaten feed. The organic content in the feed and the possibility of anaerobic conditions at the bottom of the reservoir waters can generate the decomposition process, which produces methane gas which is also a greenhouse gas. The floating net cages in the Sutami Reservoir, Indonesia, are about 173 ha in width, with the fish feed requirement of around 77.97 kg ha-1 day-1. Estimated uneaten feed and wasted to the bottom of the waters is about 2.3 g m-2 day-1, and methane gas emission from the feed waste is about 0.9 g m-2 day-1. This methane gas can contribute to methane gas in the atmosphere, so it is necessary to manage aquaculture, which has the potential to contribute methane gas as a greenhouse gas. Application of double nets on floating net cages can develop to attempt the reduction of feed waste in the fish farming system.